Parity-violating electron scattering - Kowalski, S. (HNPS Advances in Nuclear Physics, 2020)
Parity violating electron scattering has been a very useful tool for probing the structure of neutral currents and providing detailed information on electroweak form factors. A pioneering SLAC measurement in the mid-70’s provided an important early test of the Standard Model. Modern electron accelerators provide high intensity (>100 μA), CW beams with polarizations as high as 85%. Experiments such as SAMPLE, A4, HAPPEX and G0 have exploited these capabilities and obtained new information on electroweak strange form factors in the Q2 range of 0.1-1.0 GeV2. That activity continues. Other experiments are designed to provide stringent tests of the Standard Model. E-158 at SLAC recently measured the weak charge of the electron. Qweak is a challenging new experiment at JLAB which is designed to measure the weak charge of the proton. This will probe for physics beyond the Standard Model corresponding to energy scales of more than 5TeV.